Regulation of the Nrf2/HO-1 axis by mesenchymal stem cells-derived extracellular vesicles: implications for disease treatment - Su, Hua; Wang, Zhongan; Zhou, Lidan; Liu, Dezhi; Zhang, Nian (Frontiers in Cell and Developmental Biology, 2024)
This comprehensive review inspects the therapeutic potential of mesenchymal stem cell-derived extracellular vesicles (MSC-EVs) across multiple organ systems. Examining their impact on the integumentary, respiratory, cardiovascular, urinary, and skeletal systems, the study highlights the versatility of MSC-EVs in addressing diverse medical conditions. Key pathways, such as Nrf2/HO-1, consistently emerge as central mediators of their antioxidative and anti-inflammatory effects. From expediting diabetic wound healing to mitigating oxidative stress-induced skin injuries, alleviating acute lung injuries, and even offering solutions for conditions like myocardial infarction and renal ischemia-reperfusion injury, MSC-EVs demonstrate promising therapeutic efficacy. Their adaptability to different administration routes and identifying specific factors opens avenues for innovative regenerative strategies. This review positions MSC-EVs as promising candidates for future clinical applications, providing a comprehensive overview of their potential impact on regenerative medicine.